Respuesta :

Answer:

y = 4 * 3^(x-3)

Step-by-step explanation:

We have 3 data points.

Looking at the y values

We notice that the sequence is geometric. We go up by 3 each time

12*3 = 36

36*3 = 108

A geometric sequence is of the form

y = a1 ( 3) ^(x)

Pick a point to help determine a1

12 = a1 ( 3) ^4

12 = a1 * 81

Divide each side by 81

12/81 = a1

4/27 = a1

y = 4/27  * (3)^x

Let's check

y = 4/27 ( 3)^6

  = 108

We now have an equation

1/27 = 3^-3

y = 4 * 3^-3 * 3^x

Rewriting

y = 4 * 3^(x-3)

I like this equation better because it is simpler